Psychology first course teacher’s and student’s conceptions about reading - Villalonga Penna, María Micaela (2019)
In this paper, we consider the reading material of the first year of the Psychology degree of a public university and we describe the teacher´s and student´s conceptions in relation to this. We interviewed teachers and incoming students of the aforementioned career and we collected material from the different subjects of the first year. We analyze interviews and reading material in light of categories that emerge from the theoretical framework and we took into account emerging ones. We find that the reading material included academic texts derived from scientific texts predominantly expository. In addition, we found differences in terms of the knowledge about textual classes between teachers with more and less experience and among students according to their academic performance.